2018
DOI: 10.3389/fphys.2018.00477
|View full text |Cite
|
Sign up to set email alerts
|

Role of ROS and Nutritional Antioxidants in Human Diseases

Abstract: The overproduction of reactive oxygen species (ROS) has been implicated in the development of various chronic and degenerative diseases such as cancer, respiratory, neurodegenerative, and digestive diseases. Under physiological conditions, the concentrations of ROS are subtlety regulated by antioxidants, which can be either generated endogenously or externally supplemented. A combination of antioxidant-deficiency and malnutrition may render individuals more vulnerable to oxidative stress, thereby increasing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
477
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 651 publications
(491 citation statements)
references
References 173 publications
(218 reference statements)
7
477
1
6
Order By: Relevance
“…Furthermore, we speculate that the low consumption of vitamin E, selenium, and zinc may have affected protein supplementation responses, since antioxidants from the diet have the potential to block the generation of free radicals contributing to the slowing of the aging process. 32 respectively, P < 0.05). Zinc acts (as well as cysteine and selenium) as an antioxidant cofactor, since it is necessary for the proper functioning of GSH and SOD.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Furthermore, we speculate that the low consumption of vitamin E, selenium, and zinc may have affected protein supplementation responses, since antioxidants from the diet have the potential to block the generation of free radicals contributing to the slowing of the aging process. 32 respectively, P < 0.05). Zinc acts (as well as cysteine and selenium) as an antioxidant cofactor, since it is necessary for the proper functioning of GSH and SOD.…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies have demonstrated the benefits of whey protein on OS; however, these responses do not outweigh the adaptations provided by the training. Furthermore, we speculate that the low consumption of vitamin E, selenium, and zinc may have affected protein supplementation responses, since antioxidants from the diet have the potential to block the generation of free radicals contributing to the slowing of the aging process . In fact, TRAP and SOD changes had a positive correlation with zinc consumption ( r = 0.31 and r = 0.34, respectively, P < 0.05).…”
Section: Discussionmentioning
confidence: 93%
“…Numerous studies have consistently suggested the existence of a bidirectional relationship between oxidative stress inflammation and these conditions (Demyttenaere et al, 2009;Liu et al, 2018;Prenderville, Kennedy, Dinan, & Cryan, 2015;Straub & Cutolo, 2018). Previous investigations have suggested that oxi-inflammatory states triggered by depression and/or chronic psychological stress appear to be associated with the elevation of reactive oxygen species (ROS) (Lopresti, Maker, Hood, & Drummond, 2014), including superoxide anion levels produced by NADPH oxidase activation or some impairment in superoxide dismutase (SOD) enzymes (Seo et al, 2012;Uchihara, Tanaka, Asano, Tamura, & Mizushima, 2016;Xie et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Overproduction of ROS plays a role in the development of common disorders such as diabetes mellitus, dyslipidemia, obesity, chronic obstructive pulmonary disorder, and cancer. [1][2][3] Polycystic ovary syndrome (PCOS), one of the most common causes of endocrine infertility, is characterized by reproductive and metabolic disturbances as well as disruption of the REDOX state. [4][5][6][7][8][9][10][11][12][13] Studies conducted in women with PCOS revealed increased oxidant and antioxidant markers in the blood, although the results were inconsistent because of the high heterogeneity of patients (age, body mass index, severity of hyperandrogenism) and tests used to evaluate oxidative stress.…”
Section: Introductionmentioning
confidence: 99%